High-level event detection in broadcast sports video - Rea, Niall (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2005)
This thesis investigates semantic analysis of broadcast sports footage. A domain dependent sports video model is proposed. Under this model, the game semantics can be derived according to their relationship with the sequence of dynamic events that occur in the sport and the evolution of the spatio-temporal behaviour of a relevant object. Snooker and tennis are targeted as typical broadcast sports footage for the purpose of this research. The problem focus is to automatically extract semantically meaningful events and to convey a useful representation to the user.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin